Replacement of Infected Aortic Prosthetic Graft with Aortic Homograft after Heart Transplantation: 13‐Year Follow‐Up. Issue 3 (28th March 2013) - Macedo, Francisco Igor B.; Salerno, Tomas A.; Pham, Si M.
Abstract Acute ascending aortic dissection (AAAD) is a rare complication after orthotopic heart transplantation. We report a patient with AAAD after heart transplantation in whom repair was complicated by infection of the ascending aortic prosthetic graft. This was successfully managed by re‐do replacement with two cryopreserved aortic homografts. Despite extensive calcification in the wall, the homografts show no aneurysm or dilation after 10 years. doi: 10.1111/jocs.12097 (J Card Surg 2013;28:312–314)